2020
DOI: 10.1016/j.clinthera.2020.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Versus Zoledronic Acid in the Prevention of Skeletal-related Events in Vulnerable Cancer Patients: A Meta-analysis of Randomized, Controlled Trials

Abstract: Bone metastases from solid tumors and multiple myeloma (MM) represent an important source of morbidity. The present meta-analysis was performed with the purpose of comparing the efficacy and tolerability of denosumab versus zoledronic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The benefit of preventing SREs in patients with bone metastases achieved by Dmab was consistently reported across included clinical trials with no interstudy heterogeneity. Previous meta-analyses have also confirmed the advantage of Dmab over ZA in delaying the onset of SREs [21][22][23] . SREs secondary to bone metastases such as pathological fracture, spinal cord compression, radiation or surgery to bone commonly occur clinically 28 , resulting in reduced survival, higher functional independence rates and dramatically lower health-related quality of life 29 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The benefit of preventing SREs in patients with bone metastases achieved by Dmab was consistently reported across included clinical trials with no interstudy heterogeneity. Previous meta-analyses have also confirmed the advantage of Dmab over ZA in delaying the onset of SREs [21][22][23] . SREs secondary to bone metastases such as pathological fracture, spinal cord compression, radiation or surgery to bone commonly occur clinically 28 , resulting in reduced survival, higher functional independence rates and dramatically lower health-related quality of life 29 .…”
Section: Discussionmentioning
confidence: 73%
“…Growing evidence suggests that Dmab is superior in terms of efficacy 17,18 , safety 5 and even cost-P r e p r i n t effectiveness 19,20 over ZA. Published meta-analyses comparing the efficacy between Dmab and ZA for treatment of bone metastases in patients with solid tumors demonstrated that Dmab was better than ZA in preventing complications and delaying the onset of skeletal-related events (SREs) [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…When compared to ZA, denosumab was significantly better at delaying the time to the first skeletal-event and reducing pain. Overall survival and disease progression were similar in both groups [59] , [60] . These results are in accordance with our study regarding the time to the first skeletal-related event.…”
Section: Discussionmentioning
confidence: 74%
“…However, increased incidence of osteonecrosis of the jaw was associated with denosumab as compared to zoledronic acid. A meta-analysis showed similar results for denosumab in the prevention of skeletal-related adverse events as compared to zoledronic acid [ 73 ]. Moreover, an RCT by Smith et al (2012) tested denosumab for the prevention of bone metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%